Penyelesiaan Sengketa Kontrak Konstruksi pada Proyek Pemerintah yang mencantumkan Klausula Arbitrase - beri yandie (Universitas Internasional Batam, 2019)
Arbitration is an alternative mechanism to settle a construction dispute outside the court based on a Construction Work Contract by using an Arbitration clause made in writing by the parties to the dispute. Arbitration is much in demand in handling disputes over construction work contracts because it is believed to be more effective and efficient. The purpose of this research is to discuss the legal consequences of inserting the Arbitration Clause in a construction work contract under Law No. 2 of 2017 concerning Construction Services in the State Gazette of the Republic of Indonesia Number 11 and Additional State Gazette of the Republic of Indonesia Number 6018 in lieu of Law No. 18 of 1999 concerning Construction Services in theState Gazette Number 54 and Additional State Gazette Number 3833. In addition, it aims to analyze the dispute resolution process in a construction contract based on Law No. 30 of 1999 concerning Arbitration and ADR. It uses a normative legal research with a qualitative approach to analize the collected data. It finds that the legal consequences of the inclusion of arbitration clauses in construction work contracts is that the dispute issue through arbitration. Article 70 of Law No.30 of 1999 may be used by the parties to a request for cancellation of the arbitration award at the State Court. Construction work contracts are the domain of private law.